Peran Sekolah dalam Membentuk Keterampilan Wirausaha Berbasis Tauhid di SD Entrepreneur Muslim Alif-A Piyungan Bantul Yogyakarta - Widia Riska Wahyuni; Wiji Hidayati (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
This study aims to determine the roles and ways undertaken by schools in inculcating the character of entrepreneurial-based tauhid in order to be able to help learners gain knowledge about entrepreneurship from early childhood as well as help to build quality of Islamic School with high trust and quality. This research is a qualitative research conducted at Entrepreneur Elementary School Muslim ALIF-A Piyungan Bantul Yogyakarta. The data is collected using observation, interviews and documentation. The results of this study are: firstly, the role of schools in the formation of students’ entrepreneurial skills is demonstrated by activities in schools to acquire knowledge and skills by assisting learners in shaping character and personality, and be able to interact with their environments through integrated thematic learning. Learners have to be active, and are encouraged to recognize and accept the values of entrepreneurship in developing the ability of learners to perform daily activities. Secondly, in the formation of entrepreneurial character, the school has six basic principles, they are: educative, effective, strategic, empirical, leadership, and productive through three learning zones, namely spiritual zone, learning zone, and entrepreneur zone based on the character of each program. Thirdly, the results of the system can be seen from the students’ attitude of independent, tawakkal, creative, innovative, confident, discipline, have a sense of responsibility and tolerate others.